1995
DOI: 10.1111/j.1399-3011.1995.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationships of dermorphin analogues containing N‐substituted amino acids in the 2‐position of the peptide sequence

Abstract: A series of dermorphin analogues containing an N-alkylated amino-acid residue Xaa in the 2-position of the peptide sequence was synthesized (Xaa = N-methylalanine, proline, pipecolic acid, N-methylphenylalanine, 1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid [Tic]). These peptides have the potential of assuming a cis Tyrl-Xaa2 peptide bond. Their in vitro opioid activity profiles were determined in p-and b-receptorrepresentative binding assays and bioassays. Aside from [ ~-Pro~]dermorphin, all analogues show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The best substituents for position 2 turned out to be d ‐Ala and N‐methylated Ala or Gly residues. Much earlier, structure–activity relationship studies of dermorphins, atypical μ‐selective opioids from frog skin extracts, revealed the crucial role of the d ‐amino acid residue in the 2‐position for opioid activity [25]. Interestingly, analogues with L‐configuration in this position were completely inactive [26], but the activity was restored when the position 2 residue was N‐methylated [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best substituents for position 2 turned out to be d ‐Ala and N‐methylated Ala or Gly residues. Much earlier, structure–activity relationship studies of dermorphins, atypical μ‐selective opioids from frog skin extracts, revealed the crucial role of the d ‐amino acid residue in the 2‐position for opioid activity [25]. Interestingly, analogues with L‐configuration in this position were completely inactive [26], but the activity was restored when the position 2 residue was N‐methylated [25].…”
Section: Discussionmentioning
confidence: 99%
“…Much earlier, structure–activity relationship studies of dermorphins, atypical μ‐selective opioids from frog skin extracts, revealed the crucial role of the d ‐amino acid residue in the 2‐position for opioid activity [25]. Interestingly, analogues with L‐configuration in this position were completely inactive [26], but the activity was restored when the position 2 residue was N‐methylated [25]. Due to isomerization around Tyr‐Pro peptide bond, EMs exist as a mixture of cis and trans rotamers and despite the extensive research, it is still unknown whether they adopt the cis or trans configuration around this bond when bound to the receptor [27].…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown enhanced potency19–22 and new receptor subtype selectivity 23–25. For example, N‐methylated cyclic RGD peptides22 and dermorphin analogs26 have been shown to be more potent following mono N‐methylation. Multiple N‐Methylation (MNM) is an approach where a library of all possible N‐methylated peptide analogs, based on the sequence of a linear or cyclic bioactive peptide, is synthesized and screened to select an active N‐methylated analog 17.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectrum of fatty hydrazides shows absorption bands for the primary amine N-H stretching at 3318. 8 The disappearance of absorption bands of the primary amine N-H stretching and N-H bending indicated that the reaction occurred at the NH 2 group. However, a weak absorption band of primary amine N-H stretching was observed with 0.003 mol KOH at frequencies 3343.…”
Section: Effect Of Koh Loadingmentioning
confidence: 99%
“…Many N-alkylation methods have been reported by Salvatore and co-workers, 2001 7 . N-methylated amines hold critical importance in amine chemistry 8 . Recently, Badr and co-workers 2010 reported direct N-methylation of primary amines using dimethyl sulfate with 80 yield.…”
Section: Introductionmentioning
confidence: 99%